Association of blaVIM-2, blaPDC-35, blaOXA-10, blaOXA-488 and blaVEB-9 β-Lactamase Genes with Resistance to Ceftazidime–Avibactam and Ceftolozane–Tazobactam in Multidrug-Resistant Pseudomonas aeruginosa - Mazen A. Sid Ahmed; Faisal Ahmad Khan; Hamad Abdel Hadi; Sini Skariah; Ali A. Sultan; Abdul Salam; Abdul Latif Al Khal; Bo Söderquist; Emad Bashir Ibrahim; Ali S. Omrani; Jana Jass (Antibiotics, 2022)
Ceftazidime–avibactam and ceftolozane–tazobactam are approved for the treatment of complicated Gram-negative bacterial infections including multidrug-resistant (MDR) Pseudomonas aeruginosa. Resistance to both agents has been reported, but the underlying mechanisms have not been fully explored. This study aimed to correlate β-lactamases with phenotypic resistance to ceftazidime–avibactam and/or ceftolozane–tazobactam in MDR-P. aeruginosa from Qatar. A total of 525 MDR-P. aeruginosa isolates were collected from clinical specimens between 2014 and 2017. Identification and antimicrobial susceptibility were performed by the BD PhoenixTM system and gradient MIC test strips. Of the 75 sequenced MDR isolates, 35 (47%) were considered as having difficult-to-treat resistance, and 42 were resistant to ceftazidime–avibactam (37, 49.3%), and/or ceftolozane–tazobactam (40, 53.3%). They belonged to 12 sequence types, with ST235 being predominant (38%). Most isolates (97.6%) carried one or more β-lactamase genes, with blaOXA-488 (19%) and blaVEB-9 (45.2%) being predominant. A strong association was detected between class B β-lactamase genes and both ceftazidime–avibactam and ceftolozane–tazobactam resistance, while class A genes were associated with ceftolozane–tazobactam resistance. Co-resistance to ceftazidime–avibactam and ceftolozane–tazobactam correlated with the presence of blaVEB-9, blaPDC-35, blaVIM-2, blaOXA-10 and blaOXA-488. MDR-P. aeruginosa isolates resistant to both combination drugs were associated with class B β-lactamases (blaVIM-2) and class D β-lactamases (blaOXA-10), while ceftolozane–tazobactam resistance was associated with class A (blaVEB-9), class C (blaVPDC-35), and class D β-lactamases (blaOXA-488).